Key digitalization effects and possible losses - V. F. Ukolov; V. Ya. Afanasev; V. V. Cherkasov (Вестник университета)
The key effects of digitalization and possible losses during its use have been considered. It has been shown, that digitalization expands the possibilities of information when translating it into a digital form of knowledge and high-quality updating of production. It has been proven, that digitalization is not an end in itself, but an auxiliary tool for the implementation of the economic strategy and industrial policy of the state, increasing production efficiency and should be assessed taking into account this indicator. The expediency of the practical use of digitalization in the number of effective tools for creating flexible industries, the transition to high-performance, industrial ecosystems and industrialization has been substantiated. The possible losses from digitalization while increasing the dependence of production on digital technologies and reducing the role of the human factor have been shown.